2005
DOI: 10.1080/15572536.2006.11832771
|View full text |Cite
|
Sign up to set email alerts
|

Heterothallic mating observed between Mexican isolates of Glomerella lindemuthiana

Abstract: Although several reports have described the occurrence of the teleomorphic state of Glomerella lindemuthiana (anamorph, Colletotrichum lindemuthianum), there has been a lack of continuity in this research. To identify G. lindemuthiana isolates capable of developing the teleomorphic state, 19 Mexican isolates were analyzed. Three types of response were observed: (i) negative, where only mycelial growth with or without acervuli was observed; (ii) potential, where in addition to the above, spherical perithecia-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
1
16
0
3
Order By: Relevance
“…Sacc.) and more recent reports on different species within the genus Glomerella (Cisar et al 1996;Cisar and TeBeest 1999;Vaillancourt and Hanau 1999;Vaillancourt et al 2000;Rodríguez-Guerra et al 2005) suggest that control of sexual reproduction within this genus is different from that described for other fi lamentous ascomycetes.…”
Section: Analysis Of the Mat1-2-1 Gene Of Colletotrichum Lindemuthianummentioning
confidence: 93%
See 4 more Smart Citations
“…Sacc.) and more recent reports on different species within the genus Glomerella (Cisar et al 1996;Cisar and TeBeest 1999;Vaillancourt and Hanau 1999;Vaillancourt et al 2000;Rodríguez-Guerra et al 2005) suggest that control of sexual reproduction within this genus is different from that described for other fi lamentous ascomycetes.…”
Section: Analysis Of the Mat1-2-1 Gene Of Colletotrichum Lindemuthianummentioning
confidence: 93%
“…Amplifi cation of the conserved HMG region of the MAT1-2-1 gene in C. lindemuthianum isolates MU 03 and DGO 02 revealed that the MAT1-2-1 idiomorph was present in both partners of the mating pair (Rodríguez-Guerra et al 2005). To extend this result, isolates of Colletotrichum from different plant species were analyzed using degenerate primers, and the MAT1-2-1 gene was found to be present in all isolates tested (Fig.…”
Section: Analysis Of the Mat1-2-1 Gene Of Colletotrichum Lindemuthianummentioning
confidence: 95%
See 3 more Smart Citations